A grammar of Guìqióng a language of Sichuan - Jiang, Li 1970- (Brill, 2015)
Jiang Lì describes the grammar of Guìqióng, a hitherto undocumented language spoken by alpine people in K?ngdìng county, China. Guìqióng has a lot to offer in its phonology, verbal and nominal morphology, syntax and glossary, distinguishing itself from the neighbouring Tibetan, Chinese, Qiangic and Loloish languages. 0The newly discovered features of Guìqióng include breathy vs. modal voice, indefinite number, ablative, ergative, instrumental, dative and genitive case markers, topic and emphatic markers, the diminutive suffixes, the pronominal and deictic systems, demonstratives and numerals, a rich store of differentiated copular verbs expressing equationality, inchoative, animacy vs. inanimacy, dependent existence and negation, verbal affixes indicating directions, present tense of experienced perceptions, gnomic tense, perfective vs. imperfective aspect, modality and evidentiality
Includes bibliographical references and index
Keywords: Grammatik; Guiqiong language / Grammar; Guiqiong -- Sprache